Board Diversity as a Determinant of Corporate Social Responsibility (CSR) in Malaysian Banks - Mohd Waliuddin, Mohd Razali; Mohd Azim, Tahir; Mohd Firdaus, Zakaria; Damien Lee, Lung Yau; Chang, Jin Quan (HRMARS, 2026)
The impact of board diversity on corporate social responsibility (CSR) remains unclear, raising questions about how diverse leadership influences ethical and sustainable business practices. Under stakeholder theory, board diversity influences CSR by potentially enhancing responsiveness to the interests of a broader range of stakeholders. This study is purposely to examine the relationship between board diversity and Corporate Social Responsibility (CSR) in Malaysian bank. Final sample of 34 Malaysian banks were collected. All non-financial and financial data were collected from the annual report. Board diversity in this study consist age, gender, educational level, independence and size. Board educational level and board size show a positive relationship with CSR disclosure, but this significance is observed only in NonIslamic Banks. In contrast, Islamic Banks show no significant relationship, suggesting that higher education and larger board size enhance CSR practices primarily in Non-Islamic contexts due to greater diversity, experience, and implementation capacity. This study helps investors and managers understand how board diversity positively influences CSR disclosure, especially in Non-Islamic banks, aiding better investment and management decisions. It also supports academics by offering insights into CSR practices in Malaysia and highlights how CSR can enhance company image, attract investors, and improve overall performance.